Perbandingan Hasil Perhitungan Jumlah Trombosit Metode Manual Menggunakan Pipet Thoma Dan Tabung Reaksi - Ardiansah Hasin (Jurnal Media Laboran, 2017)
This research is based on the existence of two blood dilution methods commonly used in the laboratory that is blood dilution using thoma pipette and test tube. The purpose of this research is to know the difference of calculation result of thrombocyte count with blood dilution using thoma pipette and test tube. This research is a laboratory observation research where the sample is examined 20 times. From the research that has been done on blood samples of EDTA, obtained the total number of platelets with blood dilution using thoma pipette is 6,284,000 with mean 314,200, while the total number of platelets using reaction tube is 6,456,000 with mean 322,800. Based on the results of research conducted 20 times on samples of EDTA blood obtained t count value (1.443) smaller than t table (2.024) or (t <t table), so it can be concluded that there is no significant difference in results Platelets with blood dilution using thoma pipettes and test tubes. Based on the result of research, it is suggested that blood dilution using thoma pipette and reaction tube can be used to calculate platelet count.